Concurrent waterlogging and anthracnose-twister disease in rainy-season onions (Allium cepa): Impact and management - Salunkhe, Vanita Navnath; Gedam, Pranjali; Pradhan, Aliza; Gaikwad, Bhaskar; Kale, Rajiv; Gawande, Suresh (Frontiers in Microbiology, 2022)
Waterlogging and anthracnose-twister disease are significant obstacles in rainy-season onion cultivation. As a shallow-rooted crop, onions are highly sensitive to waterlogging. Wherever rainy-season onion cultivation has been undertaken, the anthracnose-twister disease complex is also widespread across the world in addition to waterlogging. Waterlogging is the major predisposing factor for anthracnose and other fungal diseases. However, studies on the combined stress impact on onions have been ignored. In the present review, we have presented an overview of the anthracnose-twister disease, the waterlogging effect on host physiology, host-pathogen interaction under waterlogging stress, and appropriate management strategies to mitigate the combined stress effects. Crucial soil and crop management strategies can help cope with the negative impact of concurrent stresses. Raised bed planting with drip irrigation, the use of plant bio-regulators along with nutrient management, and need-based fungicide sprays would be the most reliable and feasible management options. The most comprehensive solution to withstand combined stress impacts would be a genetic improvement of commercial onion cultivars.